COMPETIVENESS OF CONSUMER PRODUCTS AND SERVICES AND ITS CONNECTION WITH COMPETITIVENESS OF ENTREPRENEURIAL STRUCTURES AS A WHOLE - D. S. Bichoyeva (Russian Journal of Economics and Law, 2011)
The article develops some preconditions required for activation of researches along the lines of mechanism formation supporting the stable process of increasing the competitiveness of organizations and their products, deep theoretical and methodological analysis of conceptions «competitiveness», «competitiveness of organization», «competitiveness of consumer products and services», grounds the efficient methods and tools for competitiveness management up to micro-level in real time and space measurements. The work introduces the approach to evaluation, criteria and index of competitiveness up to micro- level. Trade was chosen to specify the study of a certain branch of economy.